Shifting priorities in Russia's foreign and security policy - Kanet, Roger E.; Piet, Remi (Global interdisciplinary studies series, 2014)
Given the resurgence of Russian economic capabilities and of Russia's role as a regional, even global, political actor, much of the literature written more than 4-5 years ago is already dated.